Groundwater recharge estimation in Table Mountain Group aquifer systems with a case study of Kammanassie area - Wu, Yong (University of the Western Cape, 2013)
Philosophiae Doctor - PhD === The focus of this study was on recharge mechanisms and recharge estimation within the Table Mountain Group area. The study evaluated recharge processes and recharge estimation methods in the Table Mountain Group aquifer systems. === South Africa